VIRTUAL DELIVERY OF ELEMENTARY TEACHERS IN THE NEW NORMAL: PRACTICES AND IMPLEMENTATION - Norcelyn C. Batalla; Jeneth C. Day Onan; Rizza A. Tano; Genesis G. Genelza (Galaxy International Interdisciplinary Research Journal, 2023)
The online-based learning system is a current policy established by the Philippine government in all schools as a result of the COVID-19 pandemic. Shifting face-to-face schools with an online learning-based system creates problems, especially for elementary teachers. This study investigates elementary school teachers’ practices in the new normal. The BEED - Generalist researchers employed phenomenological research and purposefully selected participants who were thoroughly knowledgeable to gather essential data about effective methods of virtual delivery. The data was collected through an interview of ten elementary teachers in Magugpo, Pilot, Central Elementary School, using a researcher-made interview guide. Ten essential themes are being gathered, and these are the following: Encountering intermittent internet connection, Observing the struggles of the students, Experiencing increasing student participation, Having doubts about the student’s output, Extended extra time to learn the virtual platform, Employed engaging activities, Aligned competencies, and strategies, Demonstrated resiliency, Seeing positive thinking as good mindset, Embracing educational shift and trends, and Adapting positively to changes. The result indicates that the elementary school teachers’ practices are effective in virtual classrooms, making students more engaged and actively participating in the class. It is recommended that the result be utilized, improved, and implemented to ensure the effectiveness of handling the online course.